Facially amphiphilic polyionene biocidal polymers derived from lithocholic acid - Mitra S. Ganewatta; Md Anisur Rahman; Louis Mercado; Tinom Shokfai; Alan W. Decho; Theresa M. Reineke; Chuanbing Tang (Bioactive Materials, 2018)
Bacterial infections have become a global issue that requires urgent attention, particularly regarding to emergence of multidrug resistant bacteria. We developed quaternary amine-containing antimicrobial poly(bile acid)s that contain a hydrophobic core of lithocholic acid in the main-chain. Interestingly, by choosing appropriate monomers, these cationic polymers can form core-shell micelles. These polymers exhibited biocidal activity against both Gram-positive and Gram-negative bacterial species. It is demonstrated that the micelles can deliver hydrophobic antibiotics that functionally have dual antimicrobial activities. Cytotoxicity assays against HeLa cells showed dosage-dependent toxicity for polymers with longer linkers.